Electroluminescent device, polynuclear copper cluster complex guest material, and preparation method and application of polynuclear copper cluster complex guest material

Through the multi-core copper cluster complex material synthesized based on fluorine-containing tridentate phosphine ligand, the problem of heavy metal materials being expensive and polluted in the environment is solved, and the electroluminescent performance is achieved with high efficiency and low cost. It is suitable for the luminescent layer material of evaporated electroluminescent devices.

CN119775313AActive Publication Date: 2025-04-08HEILONGJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411991066.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Heavy metal materials are expensive and pollute the environment. Due to the distorted structure of the multi-core copper cluster complex, the excited state is prone to annihilation, resulting in low efficiency.

Method used

By synthesizing the multi-nuclear copper cluster complex guest material based on fluorine-containing tridentate phosphine ligand units, the number and coordination conditions of fluorine atoms are changed, and a variety of fluorine-containing tridentate phosphine multi-nuclear copper cluster complex materials are prepared. Using its excellent photoluminescent properties as the luminescent layer guest material, evaporated electroluminescent devices with high external quantum efficiency, high brightness, and low brightness voltage are prepared.

Benefits of technology

The electroluminescent performance with high external quantum efficiency, high brightness and low brightness voltage is achieved, the luminescence efficiency and brightness of organic electroluminescent materials are improved, and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775313A_ABST
    Figure CN119775313A_ABST
Patent Text Reader

Abstract

The invention provides a polynuclear copper cluster complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit, and belongs to the technical field of luminescent materials. According to the invention, fluorine-containing tridentate phosphine is used as a parent, and different numbers of fluorine atoms are introduced to the parent and coordinated with copper to form the polynuclear copper cluster complex. According to the invention, a plurality of fluorine-containing tridentate phosphine polynuclear copper cluster complex materials are prepared by changing the number of fluorine atoms and different coordination conditions. The rigid multi-core copper cluster complex synthesized by using the fluorine-containing tridentate phosphine ligand has excellent photoluminescence performance, so that the rigid multi-core copper cluster complex can be used as a luminescent layer guest material to prepare an evaporation electroluminescent device with high external quantum efficiency, high brightness and low turn-on voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a multi-nuclear copper cluster complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit, a preparation method of the guest material, an application of the guest material in an electroluminescent device, and an electroluminescent device comprising the multi-nuclear copper cluster complex guest material. Background Art

[0002] Organic Light Emitting Diode (OLED) is a background-free light source that can be used for lighting and screen display. In the past few decades, the research and development of OLED has never stopped. OLED provides a new and efficient and long-lasting idea for the lighting and display fields, and is gradually replacing the technology on the market. The actual application field is becoming more and more extensive. Especially in the display industry, OLED has become the focus of attention in recent years, because the performance of OLED displays is significantly better than mature technologies such as Liquid Crystal Display (LCD).

[0003] In 1963, Pope et al. first used organic materials to convert electrical energy into light energy, which is considered to be the earliest discovery of electroluminescence. They used silver electrodes as a basis and applied direct current to anthracene single crystals to make anthracene fluoresce. However, this process requires a very high driving voltage (400V), so it cannot be applied in practice. In 1987, Tang and Van Slyke reported the preparation of a double-layer device by using tris(8-hydroxyquinoline)aluminum as the light-emitting layer and the electron transport layer, which was a major breakthrough in the development of OLEDs. When the driving voltage is less than 10V, the external quantum efficiency (EQE) of the green light-emitting device is about 1%. This work broke the obstacles to the development of OLEDs and ushered in a new era. Academia and industry have shown great interest in this pioneering work and have carried out research. According to spin statistics, in OLED devices, the formation of excitons by the recombination of charges (holes and electrons) will produce about 25% singlet excitons (S1) and 75% triplet excitons (T1), but fluorescent devices can only use 25% of S1 to emit light at most. In order to overcome this defect of low device efficiency, Baldo et al. reported an OLED device in 1998. They used fluorescent materials as the main body and red-emitting organic metal complexes as luminescent materials to achieve effective energy transfer from the main body to the guest. At the same time, due to the spin-orbit coupling effect, 100% internal quantum efficiency (Internal Quantum Efficiency, IQE) was obtained, and the reported EQE and IQE were 4% and 23%, respectively. This is a pioneering study of phosphorescent OLEDs. The value of using organic metal complexes as luminescent bodies is that they can achieve 100% IQE by enabling S1 to enter T1 through intersystem crossing (ISC) through strong spin-orbit coupling mediated by heavy metals (such as Ir and Pt) in the complex. However, heavy metal materials are not only expensive, leading to increased costs, but the potential environmental pollution is also a worrying factor. In addition, although the red and green light devices of organic metal materials show excellent performance parameters, the corresponding blue light-emitting materials still need to be improved in terms of device stability, color purity and brightness. In 2012, Adachi and his colleagues first proposed Thermally Activated Delayed Fluorescence (TADF), which ushered in a new era in the research of OLEDs. TADF materials use pure organic small molecules. When the energy level difference between S1 and T1 (Singlet-Triplet SplittingEnergies, ΔE ST) is small enough, the T1 state can pass through the reverse intersystem crossing (RISC) to the S1 state, thereby using the S1 state to emit light, and also achieve 100% IQE. In recent years, OLED display technology has been widely used in the field of small and medium-sized displays, and further development is needed in large-size displays and lighting.

[0004] The structure of OLED devices usually includes a glass substrate, anode and cathode, two injection layers, two transport layers and a particularly important light-emitting layer. Under the applied voltage, the holes generated by the anode and the electrons generated by the cathode pass through the hole injection layer, hole transport layer and electron injection layer, electron transport layer respectively, and finally recombine in the light-emitting layer to form excitons, and the formed excitons return to the ground state through radiation transition to emit light. In addition, the current OLED process preparation commonly used is evaporation and spin coating. Vacuum evaporation forms a dense film by evaporating the material under high temperature and high vacuum. It is suitable for materials with good thermal stability, but the material utilization rate is low and the cost is large. The process is relatively complex and the cost is high, which is not suitable for the preparation of large-area panels. The spin coating process is relatively simple to prepare, suitable for materials with good solubility, high material utilization rate, and suitable for the preparation of large-area panels, but the efficiency and stability of the device are poor. At present, OLED still has some problems, such as short device life, poor stability, and the current high production cost. But we believe that in the near future, these problems will be solved and made more industrialized.

[0005] Of particular interest is that the rich coordination modes and inherent copper-philic interactions of copper cluster complexes produce remarkable luminescent behaviors in the complexes, making them emerging emitters for OLEDs, with rich potential in sustainable display and lighting applications. In 2016, our group reported a tridentate phosphine copper iodide complex named TTPPCuX, which has good thermal stability and rigidity characteristics. The introduced tridentate phosphine ligand has good rigidity. When the copper cluster complex molecules are used to make evaporated devices, the device can emit yellow-green light when it is lit. This work successfully demonstrates the great potential and superiority of copper cluster complexes as optoelectronic integrated systems in various device applications, as well as the significance of ligand engineering. Summary of the invention

[0006] In view of this, in order to solve the technical problems that heavy metals are expensive and pollute the environment, and that the excited state of multi-nuclear copper cluster complexes is easily annihilated due to structural distortion, resulting in low efficiency, in the first aspect, the present invention provides a multi-nuclear copper cluster complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit, and prepares a variety of fluorine-containing tridentate phosphine multi-nuclear copper cluster complex materials by changing the number of fluorine atoms and different coordination conditions. Among them, the rigid multi-nuclear copper cluster complex synthesized using a fluorine-containing tridentate phosphine ligand has excellent photoluminescent properties, and can therefore be used as a light-emitting layer guest material to prepare a vapor-deposited electroluminescent device with high external quantum efficiency, high brightness, and low turn-on voltage.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The multi-nuclear copper cluster complex guest material is synthesized based on the fluorine-containing tridentate phosphine ligand unit. The fluorine-containing tridentate phosphine is used as the matrix, and different numbers of fluorine atoms are introduced into the matrix to form a multi-nuclear copper cluster complex through coordination with copper.

[0009] Preferably, the multi-nuclear copper cluster complex guest material is a compound having the following structural formula:

[0010]

[0011] Among them, R is receptor F.

[0012] Preferably, the multi-nuclear copper cluster complex guest material is one of the following compounds I to V:

[0013]

[0014] In the second aspect, the present invention provides a method for preparing the above-mentioned multi-nuclear copper cluster complex guest material, using o-dibromobenzene or p-fluoro-o-dibromobenzene as a raw material and diphenylphosphine to synthesize a monophosphine monobromine ligand, which is then reacted with phenyl dichlorophosphine to form a fluorine-containing tridentate phosphine ligand, and finally coordinated with cuprous iodide to prepare it.

[0015] Preferably, the method specifically comprises the following steps:

[0016] Step (1), adding diphenylphosphine to o-dibromobenzene or p-fluoro-o-dibromobenzene compound to obtain monophosphine monobromine ligand;

[0017] Step (2), adding phenylphosphine dichloride to the monophosphine monobromine ligand prepared in step (1) to obtain a fluorine-containing tridentate phosphine ligand;

[0018] Step (3), adding the fluorine-containing tridentate phosphine ligand obtained in step (2) and cuprous iodide into a solvent, reacting at room temperature to obtain a reaction solution;

[0019] Step (4), post-treating the reaction solution to obtain a multi-nuclear copper cluster complex guest material.

[0020] Preferably, the reaction temperatures of step (1) and step (2) are -120°C and -78°C, respectively.

[0021] Preferably, the molar ratio of the fluorine-containing tridentate phosphine ligand to the cuprous iodide is 1:(1-12).

[0022] In a third aspect, the present invention provides the use of the multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit in an electroluminescent device.

[0023] Preferably, the multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit is used as a light-emitting layer in the electroluminescent device.

[0024] In a fourth aspect, the present invention provides an electroluminescent device, comprising a light-emitting layer, wherein the light-emitting layer contains the above-mentioned multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit.

[0025] By changing the number of fluorine atoms and different coordination conditions, a variety of fluorine-containing tridentate phosphine multinuclear copper cluster complex materials are prepared. Among them, the use of fluorine-containing tridentate phosphine ligands to synthesize rigid multinuclear copper cluster complexes has excellent photoluminescence properties, so it can be used as a guest material for the light-emitting layer to prepare a vapor-deposited electroluminescent device with high external quantum efficiency, high brightness, and low turn-on voltage. Compared with the prior art, it has the following beneficial effects:

[0026] (1) The multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit provided in the present invention has good electron transport performance. Different numbers of fluorine atoms can be modified to adjust different luminescent colors, and different electron-withdrawing abilities can adjust the distance between Cu-Cu. At the same time, the tridentate phosphine ligand is used to provide coordination sites to form a copper complex with a rigid structure, which can prepare an efficient vapor-deposited electroluminescent device.

[0027] (2) The electroluminescence peak of the multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit of the present invention is 450-550nm, which is a type of blue-luminescent organic copper cluster complex guest material. The electroluminescence peak of the tri-nuclear copper cluster complex guest material is 550-650nm, which is a type of organic copper cluster complex guest material with adjustable luminescence color, providing a new idea for the electroluminescent device of organic multi-nuclear copper cluster complex guest material.

[0028] (3) The fluorine-containing tridentate phosphine multinuclear copper cluster complex guest material in the present invention has good photoluminescence performance. In particular, the external quantum efficiency of the prepared electroluminescent device is the best among the multinuclear fluorine-containing tridentate phosphine copper cluster complex guest materials, and the current efficiency and power efficiency are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The ultraviolet spectrum and fluorescence spectrum test spectra of Example 1 and Example 2 of the present invention;

[0030] Figure 2 The ultraviolet spectrum and fluorescence spectrum test spectra of Example 3, Example 4 and Example 5 of the present invention;

[0031] Figure 3 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (I) in Example 1 of the present invention are shown;

[0032] Figure 4 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (I) in Example 1 of the present invention are shown;

[0033] Figure 5 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum diagram of the electroluminescent device of compound (II) in Example 2 of the present invention;

[0034] Figure 6 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (II) in Example 2 of the present invention;

[0035] Figure 7 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (III) in Example 3 of the present invention are shown;

[0036] Figure 8 The curves are the brightness-current efficiency relationship, the brightness-power efficiency relationship and the brightness-external quantum efficiency relationship of the electroluminescent device of compound (III) in Example 3 of the present invention.

[0037] Fig. 9 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (IV) in Example 4 of the present invention are shown;

[0038] Fig.10 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (IV) in Example 4 of the present invention;

[0039] Fig.11 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (V) in Example 5 of the present invention are shown;

[0040] Fig.12 The curves are the brightness-current efficiency relationship, the brightness-power efficiency relationship and the brightness-external quantum efficiency relationship of the electroluminescent device of compound (V) in Example 5 of the present invention.

[0041] Fig.13 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (I) in Example 1 of the present invention are shown;

[0042] Fig.14 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (I) in Example 1 of the present invention are shown;

[0043] Fig.15 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum diagram of the electroluminescent device of compound (II) in Example 2 of the present invention;

[0044] Fig.16 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (II) in Example 2 of the present invention;

[0045] Fig.17 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (III) in Example 3 of the present invention are shown;

[0046] Fig.18 The curves are the brightness-current efficiency relationship, the brightness-power efficiency relationship and the brightness-external quantum efficiency relationship of the electroluminescent device of compound (III) in Example 3 of the present invention.

[0047] Fig.19 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (IV) in Example 4 of the present invention are shown;

[0048] Fig. 20 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (IV) in Example 4 of the present invention;

[0049] Fig.21 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (V) in Example 5 of the present invention are shown;

[0050] Fig. 22The curves are the brightness-current efficiency relationship, the brightness-power efficiency relationship and the brightness-external quantum efficiency relationship of the electroluminescent device of compound (V) in Example 5 of the present invention.

[0051] Fig.23 is a single crystal structure diagram of compound (I) in Example 1 of the present invention;

[0052] Fig.24 is a single crystal structure diagram of compound (II) in Example 2 of the present invention;

[0053] Fig.25 is a single crystal structure diagram of compound (IV) in Example 4 of the present invention;

[0054] Fig.26 is a single crystal structure diagram of compound (V) in Example 5 of the present invention;

[0055] Fig. 27 This is the H NMR spectrum of compound (III) in Example 3 of the present invention. DETAILED DESCRIPTION

[0056] The multi-nuclear copper cluster complex guest material provided in the present invention, which is synthesized based on a fluorine-containing tridentate phosphine ligand unit, is a compound having the following general structural formula:

[0057]

[0058] Wherein R is the acceptor F (fluorine atom).

[0059] Preferably, the multi-nuclear copper complex guest material is selected from compounds I to V:

[0060] When R is four fluorine atoms, the compound is (I) (4FTTPPCu6I6) or (IV) (4FTTPP-TPP-Cu3I3);

[0061] When R is five fluorine atoms, the compound is (II) (5FTTPPCu6I6) or (V) (5FTTPP-TPP-Cu3I3);

[0062] When R is a fluorine atom, the compound is (III) (FTTPP-TPP-Cu3I3);

[0063] The structural formulas of the compounds are as follows:

[0064]

[0065] The present invention provides a method for preparing the above-mentioned multi-nuclear copper cluster complex guest material based on the synthesis of fluorine-containing tridentate phosphine ligand units, which uses a fluorine-containing tridentate phosphine as a matrix, uses o-dibromobenzene or p-fluoro-o-dibromobenzene as a raw material and diphenylphosphine to synthesize a monophosphine monobromine ligand, then reacts with phenylphosphine dichloride to form a fluorine-containing tridentate phosphine ligand, and finally coordinates with cuprous iodide to prepare the multi-nuclear copper cluster complex guest material.

[0066] The method for preparing the above-mentioned multi-nuclear copper cluster complex guest material based on the synthesis of fluorine-containing tridentate phosphine ligand units provided by the present invention may specifically include the following steps:

[0067] Step (1), at a temperature of -120 ° C, diphenylphosphine is added to o-dibromobenzene or p-fluoro-o-dibromobenzene to obtain a reaction solution of monophosphine monobromine ligand. Wherein, the temperature is preferably cooled to -120 ° C by mixing n-propanol and liquid nitrogen. After obtaining the monophosphine monobromine ligand, this step (1) may also include a post-treatment operation step. The post-treatment preferably includes extraction, drying and purification. The extraction is preferably to extract the reaction solution with an extractant to obtain an organic layer. The extractant is selected from acetone and dichloromethane, preferably dichloromethane. Drying is preferably to dry the organic layer with a desiccant to remove moisture, and the desiccant is not specifically limited in the present invention, such as anhydrous sodium sulfate. Purification is preferably to purify the dried organic layer by column chromatography, and the eluent of the column chromatography is a petroleum ether solvent.

[0068] Step (2), adding phenylphosphine dichloride to the reaction solution of monophosphine monobromine ligand at -78°C to obtain a fluorine-containing tridentate phosphine ligand;

[0069] Step (3), adding the obtained fluorine-containing tridentate phosphine ligand and CuI into a mixed solvent, reacting at room temperature to obtain a reaction solution;

[0070] In step (3), the solvent is selected from amide solvents, such as N,N-dimethylformamide, N,N-dimethylacetamide, aromatic hydrocarbon solvents, such as toluene or xylene, and alkane solvents, such as dichloromethane, chloroform or acetonitrile. The preferred solvent is a mixed solvent of N,N-dimethylformamide and acetonitrile.

[0071] The volume ratio of the solvent N,N-dimethylformamide to acetonitrile is 1:(1-20), preferably 1:(4-8), preferably 1:(3-5).

[0072] The molar ratio of the fluorine-containing tridentate phosphine ligand to CuI is 1:(1-12), preferably 1:(2-8), more preferably 1:(4-6), and most preferably 1:6.

[0073] The invention provides an application of the above-mentioned multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit in an electroluminescent device, especially as a light-emitting layer.

[0074] The present invention also provides an electroluminescent device prepared by using the above-mentioned multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit.

[0075] In the present invention, the electroluminescent device comprises a substrate layer, a conductive anode layer, a hole transport layer, a light emitting layer, an electron transport layer, an electron injection layer and a cathode conductive layer.

[0076] The method for preparing the electroluminescent device provided by the present invention specifically comprises the following steps:

[0077] 1. preparing a conductive anode layer;

[0078] The plastic substrate cleaned with deionized water was placed in a vacuum evaporator with a vacuum degree of 1×10 -6 mbar, and the evaporation rate was set to 0.1 nm s -1 , an anode conductive layer with a thickness of 10 nm and indium tin oxide (ITO) is deposited on a glass or plastic substrate;

[0079] 2. preparing a hole injection layer;

[0080] The hole injection layer material MoO3 is evaporated on the anode conductive layer to obtain a hole injection layer with a thickness of 6 nm;

[0081] 3. Preparation of hole transport layer;

[0082] The hole transport layer material TAPC is evaporated on the hole injection layer to obtain a hole transport layer with a thickness of 50 nm;

[0083] 4. preparing a light-emitting layer;

[0084] On the hole transport layer, a multi-core copper cluster complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit and a main material mCP are mixed to obtain a thickness of 20 nm;

[0085] 5. preparing an electron transport layer;

[0086] The electron transport layer material TPBi is evaporated on the light-emitting layer, and the thickness of the electron transport layer is 50nm;

[0087] 6. preparing an electron injection layer;

[0088] The electron injection layer material LiF is evaporated on the electron transport layer, and the thickness of the electron injection layer is 1nm;

[0089] 7. preparing a cathode conductive layer;

[0090] A cathode conductive layer with a thickness of 100 nm and a metal material is evaporated on the electron injection layer to obtain an electroluminescent device. The metal in step seven is aluminum.

[0091] The vapor-deposited electroluminescent device prepared from the multi-core copper complex guest material provided in the present invention reduces the turn-on voltage to below 3.5V and has good photoluminescent performance, while improving the luminous efficiency and brightness of the organic electroluminescent material, and can prepare an organic electroluminescent diode with excellent performance.

[0092] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0093] Example 1

[0094] In Ar, p-fluoro-o-dibromobenzene 10mmol is dissolved in anhydrous ether 50mL and is cooled to -120 ℃.Then, n-butyl lithium 10mmol is added dropwise under agitation.Then, diphenylphosphine chloride 10mmol is added dropwise.Remove cold bath, and the reaction mixture is stirred for another 16 hours.Then, water (50mL) is used to quench the reaction.Mixture is extracted with dichloromethane.Merge organic layer and use anhydrous Na2SO4 drying, remove solvent in vacuo.Purify by flash column chromatography, eluent is PE, obtain monophosphine monobromine ligand.

[0095] In Ar, monophosphine monobromine ligand 10mmol is dissolved in tetrahydrofuran 50mL and cooled to -78 ℃. Then, n-butyl lithium 10mmol is added dropwise under stirring. Then, phenyl dichlorophosphine 5mmol is added dropwise. Remove the cold bath, and stir the reaction mixture for another 16 hours. Then, quench the reaction with water (50mL). The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4, and remove the solvent in vacuo. Purify by flash column chromatography, eluent is DCM: PE (1: 5), and obtain fluorine-containing tridentate phosphine ligand.

[0096] In Ar, 1 mmol of the obtained ligand and 6 mmol of CuI were dissolved in 1 mL of N,N-dimethylformamide and 5 mL of acetonitrile and stirred at room temperature for 15 hours. The solvent was evaporated to obtain a crude complex, which was then recrystallized from a dichloromethane / n-hexane solution to obtain yellow crystals 4FTTPPCu6I6, which is compound (I).

[0097] The molecular formula of compound (I) is C 85 H 58 P6F8Cu6I6 was tested by nuclear magnetic resonance hydrogen spectrometer, and the data are as follows: 1H NMR (400MHz, CDCl3) δ7.85 (s, 4H), 7.53 (s, 2H), 7.40 (t, J = 7.3Hz, 2H), 7.36-7.23 (m, 11H), 7.20 ( t,J=7.3Hz,2H),7.13(d,J=3.5Hz,2H),7.03(t,J=7.5Hz,4H),6.92(t,J=8.4Hz,2H),6.68(s,4H).

[0098] The obtained compound (I) was tested by UV spectrum and fluorescence spectrum. The test spectrum is as follows: Figure 1 Its single crystal structure is shown in Fig.23 shown.

[0099] The obtained mixture of compound (I) and mCP is used as a light-emitting layer material to prepare an electroluminescent device, and the method is as follows:

[0100] 1. preparing a conductive anode layer;

[0101] The plastic substrate cleaned with deionized water was placed in a vacuum evaporator with a vacuum degree of 1×10 -6 mbar, and the evaporation rate was set to 0.1 nm s -1 , an anode conductive layer with a thickness of 10 nm and indium tin oxide (ITO) is deposited on a glass or plastic substrate;

[0102] 2. preparing a hole injection layer;

[0103] The hole injection layer material MoO3 is evaporated on the anode conductive layer to obtain a hole injection layer with a thickness of 6 nm;

[0104] 3. Preparation of hole transport layer;

[0105] The hole transport layer material TAPC is evaporated on the hole injection layer to obtain a hole transport layer with a thickness of 50 nm;

[0106] 4. preparing a light-emitting layer;

[0107] On the hole transport layer, a tridentate phosphine-coordinated hexanuclear copper cluster complex electroluminescent dye mixed with the host material mCP is evaporated to a thickness of 20 nm;

[0108] 5. preparing an electron transport layer;

[0109] The electron transport layer material TPBi is evaporated on the light-emitting layer, and the thickness of the electron transport layer is 50nm;

[0110] 6. preparing an electron injection layer;

[0111] The electron injection layer material LiF is evaporated on the electron transport layer, and the thickness of the electron injection layer is 1nm;

[0112] 7. preparing a cathode conductive layer;

[0113] A cathode conductive layer with a thickness of 100 nm and a metal material is evaporated on the electron injection layer to obtain an electroluminescent device. The metal in step seven is aluminum.

[0114] The structure of the electroluminescent device in this embodiment is: ITO / MoO3 (6nm) / TAPC (50nm) / mCP:4FTTPPCu6I6 (20nm) / TPBi (50nm) / LiF (1nm) / Al.

[0115] The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are as follows: Figure 3-4 shown.

[0116] Example 2

[0117] In Ar, p-fluoro-o-dibromobenzene 10mmol is dissolved in anhydrous ether 50mL and cooled to -120 ℃. Then, n-butyl lithium 10mmol is added dropwise under agitation. Then, diphenylphosphine chloride 10mmol is added dropwise. Remove the cold bath, and the reaction mixture is stirred for another 16 hours. Then, water (50mL) is used to quench the reaction. The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4. Remove the solvent in vacuo. Purify by flash column chromatography, eluent is PE, obtain monophosphine monobromine ligand.

[0118] In Ar, monophosphine monobromine ligand 10mmol is dissolved in tetrahydrofuran 50mL and cooled to -78 ℃. Then, n-butyl lithium 10mmol is added dropwise under stirring. Then, phenyl dichlorophosphine 5mmol is added dropwise. Remove the cold bath, and stir the reaction mixture for another 16 hours. Then, quench the reaction with water (50mL). The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4. Remove the solvent in vacuo. Purify by flash column chromatography, eluent is DCM: PE (1: 5), and obtain fluorine-containing tridentate phosphine ligand.

[0119] In Ar, 1 mmol of the obtained ligand and 6 mmol of CuI were dissolved in 1 mL of N,N-dimethylformamide and 5 mL of acetonitrile and stirred at room temperature for 15 hours. The solvent was evaporated to obtain a crude complex, which was then recrystallized from a dichloromethane / n-hexane solution to obtain yellow crystals 5FTTPPCu6I6, which is compound (II).

[0120] The molecular formula of compound (II) is C 85 H 56 P6F 10Cu6I6, and tested it with a nuclear magnetic resonance hydrogen spectrometer, the data are: 1 H NMR (400MHz, CDCl3) δ7.79 (dd, J=10.4, 6.7Hz, 8H), 7.39-7.27 (m, 24H), 7.18 (t ,J=7.5Hz,8H),7.00(t,J=8.0Hz,4H),6.94-6.87(m,4H),6.84(t,J=8.5Hz,8H).

[0121] The obtained compound (II) was tested by UV spectrum and fluorescence spectrum. The test spectrum is as follows: Figure 1 Its single crystal structure is shown in Fig.24 shown.

[0122] An electroluminescent device is prepared using the mixture of the obtained compound (II) and mCP as the light-emitting layer material. The method is the same as the method for preparing the electroluminescent device in Example 1, except that the mixture of the compound (II) and mCP obtained in Example 2 is used as the light-emitting layer material.

[0123] The structure of the electroluminescent device in this embodiment is: ITO / MoO3 (6nm) / TAPC (50nm) / mCP:5FTTPPCu6I6 (20nm) / TPBi (50nm) / LiF (1nm) / Al.

[0124] The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are as follows: Figure 5-6 shown.

[0125] Example 3

[0126] In Ar, p-fluoro-o-dibromobenzene 10mmol is dissolved in anhydrous ether 50mL and is cooled to -120 ℃.Then, n-butyl lithium 10mmol is added dropwise under agitation.Then, diphenylphosphine chloride 10mmol is added dropwise.Remove cold bath, and the reaction mixture is stirred for another 16 hours.Then, water (50mL) is used to quench the reaction.Mixture is extracted with dichloromethane.Merge organic layer and use anhydrous Na2SO4 drying, remove solvent in vacuo.Purify by flash column chromatography, eluent is PE, obtain monophosphine monobromine ligand.

[0127] In Ar, monophosphine monobromine ligand 10mmol is dissolved in tetrahydrofuran 50mL and cooled to -78 ℃. Then, n-butyl lithium 10mmol is added dropwise under stirring. Then, phenyl dichlorophosphine 5mmol is added dropwise. Remove the cold bath, and stir the reaction mixture for another 16 hours. Then, quench the reaction with water (50mL). The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4. Remove the solvent in vacuo. Purify by flash column chromatography, eluent is DCM: PE (1: 5), and obtain fluorine-containing tridentate phosphine ligand.

[0128] In Ar, 1 mmol of the obtained fluorinated tridentate phosphine ligand and 1 mmol of triphenylphosphine were dissolved with 6 mmol of CuI in 1 mL of N,N-dimethylformamide and 5 mL of acetonitrile, and stirred at room temperature for 15 hours. The solvent was evaporated to obtain a crude complex, which was then recrystallized from a dichloromethane / n-hexane solution to obtain yellow crystalline FTTPP-TPP-Cu3I3, which is compound (III).

[0129] The molecular formula of compound (III) is C 60 H 47 P4FCu3I3, and tested it with a nuclear magnetic resonance hydrogen spectrometer, the data is: 1 H NMR (400MHz, CDCl3) δ7.85 (s, 4H), 7.53 (s, 2H), 7.40 (t, J = 7.3Hz, 8H), 7.36-7.23 (m, 14H), 7.20 ( t,J=7.3Hz,2H),7.13(d,J=3.5Hz,8H),7.03(t,J=7.5Hz,4H),6.92(t,J=8.4Hz,2H),6.68(s,4H).

[0130] The obtained compound (III) was tested by UV spectrum and fluorescence spectrum. The test spectrum is as follows: Figure 2 Its H NMR spectrum Fig. 27 shown.

[0131] An electroluminescent device is prepared using the obtained mixture of compound (III) and mCP as the light-emitting layer material. The method is the same as the method for preparing the electroluminescent device in Example 1, except that the mixture of compound (III) and mCP obtained in Example 3 is used as the light-emitting layer material.

[0132] The structure of the electroluminescent device in this embodiment is: ITO / MoO3 (6nm) / TAPC (50nm) / mCP:FTTPP-TPP-Cu3I3 (20nm) / TPBi (50nm) / LiF (1nm) / Al.

[0133] The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are as follows: Figure 7-8 shown.

[0134] Example 4

[0135] In Ar, p-fluoro-o-dibromobenzene 10mmol is dissolved in anhydrous ether 50mL and is cooled to -120 ℃.Then, n-butyl lithium 10mmol is added dropwise under agitation.Then, diphenylphosphine chloride 10mmol is added dropwise.Remove cold bath, and the reaction mixture is stirred for another 16 hours.Then, water (50mL) is used to quench the reaction.Mixture is extracted with dichloromethane.Merge organic layer and use anhydrous Na2SO4 drying, remove solvent in vacuo.Purify by flash column chromatography, eluent is PE, obtain monophosphine monobromine ligand.

[0136] In Ar, monophosphine monobromine ligand 10mmol is dissolved in tetrahydrofuran 50mL and cooled to -78 ℃. Then, n-butyl lithium 10mmol is added dropwise under stirring. Then, phenyl dichlorophosphine 5mmol is added dropwise. Remove the cold bath, and stir the reaction mixture for another 16 hours. Then, quench the reaction with water (50mL). The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4. Remove the solvent in vacuo. Purify by flash column chromatography, eluent is DCM: PE (1: 5), and obtain fluorine-containing tridentate phosphine ligand.

[0137] In Ar, 1 mmol of the obtained ligand and 1 mmol of triphenylphosphine were dissolved with 6 mmol of CuI in 1 mL of N,N-dimethylformamide and 5 mL of acetonitrile, and stirred at room temperature for 15 hours. The solvent was evaporated to obtain a crude complex, which was then recrystallized from a dichloromethane / n-hexane solution to obtain yellow crystals 4FTTPP-TPP-Cu3I3, which is compound (IV).

[0138] The molecular formula of compound (IV) is C 60 H 44 P4F4Cu3I3, and tested it with a nuclear magnetic resonance hydrogen spectrometer, the data are: 1 H NMR (400MHz, CDCl3) δ7.79 (dd, J=10.4, 6.7Hz, 4H), 7.39-7.27 (m, 17H), 7.18 (t, J=7.5Hz,10H),7.00(t,J=8.0Hz,8H),6.94-6.87(m,2H),6.84(t,J=8.5Hz,4H).

[0139] The obtained compound (IV) was tested by UV spectrum and fluorescence spectrum. The test spectrum is as follows: Figure 2Its single crystal structure is shown in Fig.25 shown.

[0140] An electroluminescent device is prepared using a mixture of the obtained compound (IV) and mCP as a light-emitting layer material. The method for preparing an electroluminescent device is the same as the method for preparing an electroluminescent device in Example 1, except that a mixture of the compound (III) obtained in Example 4 and mCP is used as a light-emitting layer material.

[0141] The structure of the electroluminescent device in this embodiment is: ITO / MoO3(6nm) / TAPC(50nm) / mCP:4FTTPP-TPP-Cu3I3(20nm) / TPBi(50nm) / LiF(1nm) / Al.

[0142] The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are as follows: Figure 9-10 shown.

[0143] Example 5

[0144] In Ar, p-fluoro-o-dibromobenzene 10mmol is dissolved in anhydrous ether 50mL and is cooled to -120 ℃.Then, n-butyl lithium 10mmol is added dropwise under agitation.Then, diphenylphosphine chloride 10mmol is added dropwise.Remove cold bath, and the reaction mixture is stirred for another 16 hours.Then, water (50mL) is used to quench the reaction.Mixture is extracted with dichloromethane.Merge organic layer and use anhydrous Na2SO4 drying, remove solvent in vacuo.Purify by flash column chromatography, eluent is PE, obtain monophosphine monobromine ligand.

[0145] In Ar, monophosphine monobromine ligand 10mmol is dissolved in tetrahydrofuran 50mL and cooled to -78 ℃. Then, n-butyl lithium 10mmol is added dropwise under stirring. Then, phenyl dichlorophosphine 5mmol is added dropwise. Remove the cold bath, and stir the reaction mixture for another 16 hours. Then, quench the reaction with water (50mL). The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4. Remove the solvent in vacuo. Purify by flash column chromatography, eluent is DCM: PE (1: 5), and obtain fluorine-containing tridentate phosphine ligand.

[0146] In Ar, 1 mmol of the obtained ligand and 1 mmol of triphenylphosphine were dissolved with 6 mmol of CuI in 1 mL of N,N-dimethylformamide and 5 mL of acetonitrile, and stirred at room temperature for 15 hours. The solvent was evaporated to obtain a crude complex, which was then recrystallized from a dichloromethane / n-hexane solution to obtain yellow crystals 5FTTPP-TPP-Cu3I3, which is compound (V).

[0147] The molecular formula of compound (V) is C 60 H 43 P4F5Cu3I3, and tested it with a nuclear magnetic resonance hydrogen spectrometer, the data are: 1 H NMR (400MHz, CDCl3) δ7.79 (dd, J=10.4, 6.7Hz, 4H), 7.39-7.27 (m, 16H), 7.18 (t, J=7.5Hz,10H),7.00(t,J=8.0Hz,8H),6.94-6.87(m,2H),6.84(t,J=8.5Hz,4H).

[0148] The obtained compound (V) was tested by UV spectrum and fluorescence spectrum. The test spectrum is as follows: Figure 2 Its single crystal structure is shown in Fig.26 shown.

[0149] An electroluminescent device is prepared using the mixture of the obtained compound (V) and mCP as the light-emitting layer material. The method is the same as the method for preparing the electroluminescent device in Example 1, except that the mixture of the compound (V) and mCP obtained in Example 4 is used as the light-emitting layer material.

[0150] The structure of the electroluminescent device in this embodiment is: ITO / MoO3(6nm) / TAPC(50nm) / mCP:5FTTPP-TPP-Cu3I3(20nm) / TPBi(50nm) / LiF(1nm) / Al.

[0151] The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are as follows: Figure 11-12 shown.

[0152] Comparative Example: The obtained compounds (I)-(V) were used as the light-emitting layer materials to prepare an electroluminescent device. The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are shown in FIG. Figure 13-22 shown.

[0153] The present invention is described in detail above in conjunction with specific embodiments and / or exemplary examples and drawings, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A multi-nuclear copper cluster complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit, characterized in that: Taking fluorine-containing tridentate phosphine as the matrix, different numbers of fluorine atoms are introduced into the matrix, and multi-nuclear copper cluster complexes are formed by coordinating with copper.

2. The multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit according to claim 1, characterized in that: The multi-nuclear copper cluster complex guest material is a compound having the following structural formula: Among them, R is receptor F.

3. The multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit according to claim 2, characterized in that: The multi-nuclear copper cluster complex guest material is one of the following compounds I to V:

4. The method for preparing a multi-nuclear copper cluster complex guest material based on the synthesis of a fluorine-containing tridentate phosphine ligand unit according to any one of claims 1 to 3, characterized in that: The monophosphine monobromine ligand is synthesized with o-dibromobenzene or p-fluoro-o-dibromobenzene and diphenylphosphine, and then with phenylphosphine dichloride to form a fluorine-containing tridentate phosphine ligand, and finally coordinated with cuprous iodide to prepare the product.

5. The method for preparing a multi-nuclear copper cluster complex guest material based on the synthesis of a fluorine-containing tridentate phosphine ligand unit according to claim 4, characterized in that: The specific steps include: Step (1), adding diphenylphosphine to o-dibromobenzene or p-fluoro-o-dibromobenzene compound to obtain monophosphine monobromine ligand; Step (2), adding phenylphosphine dichloride to the monophosphine monobromine ligand prepared in step (1) to obtain a fluorine-containing tridentate phosphine ligand; Step (3), adding the fluorine-containing tridentate phosphine ligand obtained in step (2) and cuprous iodide into a solvent, reacting at room temperature to obtain a reaction solution; Step (4), post-treating the reaction solution to obtain a multi-nuclear copper cluster complex guest material.

6. The method for preparing a multi-nuclear copper cluster complex guest material based on the synthesis of a fluorine-containing tridentate phosphine ligand unit according to claim 5, characterized in that: The reaction temperatures of step (1) and step (2) are -120 o C and -78°C.

7. The method for preparing a multi-nuclear copper cluster complex guest material based on the synthesis of a fluorine-containing tridentate phosphine ligand unit according to claim 4, characterized in that: The molar ratio of the fluorine-containing tridentate phosphine ligand to the cuprous iodide is 1:(1-12).

8. Use of the multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit according to any one of claims 1 to 3 in an electroluminescent device.

9. The use according to claim 8, characterized in that The multi-nuclear copper cluster complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit is used as a light-emitting layer in the electroluminescent device.

10. An electroluminescent device, characterized in that: The invention comprises a light-emitting layer, wherein the light-emitting layer comprises a multi-nuclear copper cluster complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Polydentate phosphine coordination copper trihalide tri-type complex as well as synthesis method and application of polydentate phosphine coordination copper trihalide tri-type complex

    CN115433227A

  • Polynuclear copper complex based on triphenylphosphine group coordination and application thereof

    CN117209512A

  • Triphenylphosphine polynuclear copper cluster complex and electroluminescent device prepared from same

    CN117209513A

  • Aromatic amine modified tridentate phosphine coordination copper complex as well as preparation method and application thereof

    CN117659084A

  • Bipolar thermally activated delayed fluorescence material, preparation method therefor, and organic electroluminescent diode device

    WO2020211122A1